2023
DOI: 10.4236/jtst.2023.92009
|View full text |Cite
|
Sign up to set email alerts
|

Inventory of the Thermo-Physiological Behavior of Fabrics—A Review

Abstract: A comprehensive literature review was performed to create an inventory of thermal-physiological quantities for fabrics from different fiber materials, material blends, and fabric structures. The goal was to derive over-arching concepts that cannot be seen by the individual studies alone. Equations of best fits suggest non-linear changes for fabric thickness, thermal and water-vapor resistance with changes in material blend ratio. Air permeability decreases with increasing fabric density and fabric weight where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Despite a comparable porosity, the hemp-linen fabrics were lighter and had a lower bulk density, which could be attributed to the lower density of the hemp fibers [29] and also to the slightly finer weft hemp yarn (Nm 26), compared with the flax weft yarn (Nm 24). A recent comprehensive literature review [42] also stated that air permeability decreases with increased fabric density and weight, depending on the fabric materials, blend ratio, and fabric structure. Our findings were in agreement with another study [43], which found the plain weaves less permeable than the twill and satin weaves.…”
Section: Air Permeabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Despite a comparable porosity, the hemp-linen fabrics were lighter and had a lower bulk density, which could be attributed to the lower density of the hemp fibers [29] and also to the slightly finer weft hemp yarn (Nm 26), compared with the flax weft yarn (Nm 24). A recent comprehensive literature review [42] also stated that air permeability decreases with increased fabric density and weight, depending on the fabric materials, blend ratio, and fabric structure. Our findings were in agreement with another study [43], which found the plain weaves less permeable than the twill and satin weaves.…”
Section: Air Permeabilitymentioning
confidence: 99%
“…Another study [44] also revealed that the fabric weave and picking sequence had a significant effect on the fabric wetting time, water spreading speed, and also its air permeability. A recent comprehensive literature review [42] highlighted that absorbency was significantly correlated with the OMMC and therefore recommended the first as a good proxy for OMMC, which required more sophisticated measurements. OMMC correlated weakly with the fabric thickness [42].…”
Section: Air Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation